Contributing Factors on Utilization of Postnatal Care Services among the Mothers of a Rural Municipality - Parajuli, Bimala; Singh, Shreejana; Bharati, Mamata; Tandukar, Bimala; Maharjan, Reena; Bhandari, Sushila (Journal of Institute of Medicine Nepal, 2022)
Introduction: The postnatal period is a period of adjustment for both the mother and her new family member. This is a critical stage because a large proportion of maternal and neonatal deaths occur during the postnatal period. This study aimed to identify the factors that influence mothers' use of postnatal care services. Methods: Descriptive cross-sectional study was conducted among 163 mothers with children aged eight days to less than one year. The data was collected through face-to-face interviews using a semi- structured interview schedule using a non-probability purposive sampling technique. SPSS version 20 was used to analyze the data, which was then described using descriptive and inferential statistics. Results: Only 10.4% had received full postnatal care services within seven days following last childbirth. There was a significant association with respondents' education level (p-value = 0.03), history of abortion (p-value = 0.005), importance of PNC at the ANC checkup (p-value = 0.001), place of delivery (p-value = 0.004), duration of hospital stay (p-value <0.001), and health complications during recent childbirth (p value= <0.001). In binary logistic regression analysis, it showed that respondents' education more than secondary 4.6 times than up to secondary and duration of hospital stay more than 24 hours 85.5 times more than less than 24 hours were more likely to fully utilize the postnatal care services. Conclusion: Despite the accessibility and availability of postnatal care services, the level of utilization is low. Respondents fully utilize the first postnatal service but do not use the full package as recommended by protocol.